Blood and hair manganese concentrations in pregnant women from the infants' environmental health study (ISA) in Costa Rica - Mora, Ana María (2014)
Manganese (Mn), an essential nutrient, is a neurotoxicant at high concentrations. We measured Mn concentrations in repeated blood and hair samples collected from 449 pregnant women living near banana plantations with extensive aerial spraying of Mncontaining fungicide mancozeb in Costa Rica, and examined environmental and lifestyle factors associated with these biomarkers. Mean blood Mn and geometric mean hair Mn concentrations were 24.4 μg/L (8.9−56.3) and 1.8 μg/g (0.05−53.3), respectively. Blood Mn concentrations were positively associated with gestational age at sampling (β = 0.2; 95% CI: 0.1 to 0.2), number of household members (β = 0.4; 95% CI: 0.1 to 0.6), and living in a house made of permeable and difficult-to-clean materials (β = 2.6; 95% CI: 1.3 to 4.0); and inversely related to smoking (β = −3.1; 95% CI: −5.8 to −0.3). Hair Mn concentrations were inversely associated with gestational age at sampling (% change = 0.8; 95% CI: −1.6 to 0.0); and positively associated with living within 50 m of a plantation (% change = 42.1; 95% CI: 14.2 to 76.9) and Mn concentrations in drinking water (% change = 17.5; 95% CI: 12.2 to 22.8). Our findings suggest that pregnant women living near banana plantations aerially sprayed with mancozeb may be environmentally exposed to Mn.